The Bender Gradual Scoring System for Assessment of People with Intellectual Disabilities - Fabián Javier Marin Rueda; Ana Deyvis Santos Araújo Jesuíno (Paidéia (Ribeirão Preto), 2018)
Abstract The Bender Gradual Scoring System (B-GSS) is one of the main systems of visual-motor assessment used in Brazil. Studies, however, seldom address samples with atypical development. This study tested the psychometric properties of the B-GSS items in a sample of individuals with typical development (Group A; n = 198; aged between seven and 10 years old; group application) and in a sample with intellectual disabilities (Group B; n = 203; aged between 11 and 30 years old; individual application), in accordance with ethical recommendations. The results reveal figures with differential functioning. Figure 6 was biased toward group A, while figures 1 and 2 were biased toward group B. Test of the information curve indicates low precision for extreme scores. There is a need for further research to better understand how the B-GSS items work across different samples in order to verify whether such findings can be generalized to other samples.